Impact of land-use/land-cover and landscape pattern on seasonal in-stream water quality in small watersheds - Zhang, Fei; Chen, Yun; Wang, Weiwei; Jim, Chi Yung; Zhang, Zhimin; Tan, Mou Leong; Liu, Changjiang; Chan, Ngai Weng; Wang, Di; Wang, Zheng; Abdul Rahman, Haliza (Elsevier, 2022)
Changes in land use land cover (LULC) and landscape pattern in arid areas can considerably impact water quality in small watersheds. Exploring the associations between land use, landscape pattern, and riverine water quality can inform land-use planning for water-quality security. In northwest China's Jing River Watershed (JRW), water samples were collected at 67 points in 2016–2017 and analyzed. Coupled with Sentinel-2 remote-sensing images, this study calculated the Canadian Water Quality Index (CWQI) to assign the water-quality category. The Random Forest classification characterized current LULC patterns and computed landscape metrics in a riparian buffer zone. The stepwise multiple linear regression and redundancy analysis methods investigated the relationships amongst LULC, eight landscape metrics, and eight water-quality parameters. The results indicated high concentrations of total phosphorus (TP) and total nitrogen (TN) in the JRW's middle and lower reaches. For CWQI, lacking evident temporal fluctuations was contrasted by noticeable spatial variations. Intense Human activities have aggravated the deterioration of the water quality of the JRW. LULC-type changes, including Waterbody, Forest-grassland, and Farmland, imposed notable impacts on seasonal water quality. For landscape metrics, patch cohesion index (COHESION) strongly correlated with chemical oxygen demand (COD), mineralization degree (MD), and TN. By contrast, patch density (PD) correlated negatively with TN. Interspersion juxtaposition index (IJI) strongly correlated with biochemical oxygen demand after five days (BOD5). COHESION, PD, and IJI can be critical factors in predicting water-quality changes at the small-watershed scale. Our findings offered a robust scientific basis to refine regional sustainable water development strategy and rational water-resource management.